Expression of Connexin47 in oligodendrocytes is regulated by the Sox10 transcription factor. - Wegner, Michael; Glaser, Gabriele; et al. (Journal of Molecular Biology, 2006)
In the central nervous system, Connexin32 and Connexin47 are confined to oligodendrocytes where they contribute to myelin formation and maintenance, and are essential for establishing a functional glial syncytium that ensures ionic homeostasis. Despite their importance, not much is known about the regulation of connexin gene expression in oligodendrocytes. Here, we identify group E Sox proteins, in particular Sox10, as essential transcriptional regulators of both connexins. Not only was expression of Connexin32 and Connexin47 severely compromised in spinal cords of mouse mutants with reduced amounts of group E Sox proteins. Sox10 also stimulated in transient transfections the Connexin32 promoter as well as Connexin47 promoter 1b which is the main Connexin47 promoter active in the postnatal spinal cord. Detailed characterization of Connexin47 promoter 1b identified a single monomer binding site that mediated Sox10-dependent promoter activation. The region containing this binding site was also occupied by endogenous Sox10 in 33B oligodendroglioma cells. These results add Connexin47 and Connexin32 to the list of Sox10 target genes and argue that Sox10 may influence transcription of many terminal differentiation and myelination genes in oligodendrocytes as an essential regulatory component of the myelination program. © 2006 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.expres
Keywords: HMG; Krox-20; oligodendrocyte; Sox; Sry

Sox10 is an active nucleocytoplasmic shuttle protein, and shuttling is crucial for Sox10-mediated transactivation - Wegner, Michael; Stamminger, Thomas; Glaser, Gabriele; et al. (Molecular and Cellular Biology, 2002)
Sox10 belongs to a family of transcription regulators characterized by a DNA-binding domain known as the HMG box. It plays fundamental roles in neural crest development, peripheral gliogenesis, and terminal differentiation of oligodendrocytes. In accord with its function as transcription factor, Sox10 contains two nuclear localization signals and is most frequently detected in the nucleus. In this study, we report that Sox10 is an active nucleocytoplasmic shuttle protein, competent of both entering and exiting the nucleus. We identified a functional Rev-type nuclear export signal within the DNA-binding domain of Sox10. Mutational inactivation of this nuclear export signal or treatment of cells with the CRM1-specific export inhibitor leptomycin B inhibited nuclear export and consequently nucleocytoplasmic shuttling of Sox10. Importantly, the inhibition of the nuclear export of Sox10 led to decreased transactivation of transfected reporters and endogenous target genes, arguing that continuous nucleocytoplasmic shuttling is essential for the function of Sox10. To our knowledge this is the first time that nuclear export has been reported and shown to be functionally relevant for any Sox protein.
UnivIS-Import:2015-03-09:Pub.2002.med.IB.LPCIPDBI.sox10i

Sox8 is a specific marker for muscle satellite cells and inhibits myogenesis - Wegner, Michael; Glaser, Gabriele; et al. (Journal of Biological Chemistry, 2003)
Sox8 belongs to a family of transcription regulators characterized by a unique DNA-binding domain known as the high mobility group box. Many Sox proteins play fundamental roles in vertebrate development and differentiation processes. Expression of Sox8 is strong during embryonic muscle development and gradually declines postnatally. In this study, we report that in adult skeletal muscle Sox8 is confined to satellite cells. Down-regulation during myogenic differentiation was also detected in cell culture systems and occurred in parallel with down-regulation of the related Sox9. Overexpression of Sox8 or Sox9 on the other hand disrupted myoblasts in their ability to form myotubes. Concomitantly, expression of MyoD and myogenin decreased and basal as well as MyoD-induced activities of the myogenin promoter were strongly reduced in a Sox8-dependent manner. Our data suggest that Sox8 acts as a specific negative regulator of skeletal muscle differentiation, possibly by interfering with the function of myogenic basic helix-loop-helix proteins.
UnivIS-Import:2015-03-09:Pub.2003.med.IB.LPCIPDBI.sox8is